The Ordinances and Resolutions of the Mayor and City Council of Baltimore 162 (1881) - (:unkn) unknown (My University, 1881)
No. 120. An Ordinance to Prohibit the sale and use of the Toy Cartridge Pistol within the limits of the City of Baltimore: Be it enacted and ordained by the Mayor and City Council of Baltimore, That it shall not be lawful for any person or persons to sell, give away, or dispose of in any manner, what is known as "the toy cartridge pistol" within the limits of the city of Baltimore, under a penalty of ten dollars for each and every offence; the same to be collected as other fines and penalties are collected. § 2. And be it further enacted and ordained, That any person or persons who shall fire off what is known as "the toy cartridge pistol" within the limits of the city of Baltimore shall be subject to a fine of two dollars for each offence; the same to be collected as other fines and penalties are collected.
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES